Influencia del clima organizacional en el desempeño laboral de los trabajadores de la Municipalidad Distrital de Morales; durante el primer semestre del año 2015 - Silva Huamantumba, Edman Junior (2011)
The research entitled "organizational climate influence on job performance of workers of the district municipality of moral; during the first half of 2015 "it is the result of the practical application of the methodology Hernandez Sampieri Roberto raised in his book "investigation of methodology" fifth edition, with a type of descriptive correlational research and an inductive method. Also worth mentioning that a survey applied to 75 municipal employees with a questionnaire composed of 25 questions regarding the organizational environment variable and 16 questions designed to assess job performance, all in search of answer the main question posed ¿How organizational climate influences on job performance of workers of the district municipality of moral; during the first half of 2015? For what was proposed as objectives; describe the organizational climate in the district municipality of morales, analyze job performance of workers of the district municipality of morales and finally identify the elements of organizational climate that impact negatively on the performance of workers of the district municipality of morales. So was obtained as results regarding the organizational climate has been achieved diagnose which is positioned at a regular level this because there are some shortcomings such as the lack of confidence that the boss shows to its partners, like staff You can´t make their own decisions on the organization and the same benefits are not perceived properly because it does not suit your needs, consequently the policies implemented in the company is not suited to the position of staff, on the other hand regularly remuneration received by staff not suit your needs, therefore job security staff affected. But though the work environment is in good condition. With regard to job performance of workers of the district municipality of moral it is determined at a medium level, because the goals are being met regularly, like the completion of the procedures as they are not properly executed, on the other hand predisposition Staff is affected in some way, so that also affects staff working team, also your satisfaction is low, therefore the above is that job performance is positioned at a regular level. Among the main factors affecting organizational climate negatively on job performance of employees of the district municipality of moral have the lowest level of confidence prevailing in the organization, inadequate benefits, poor pay and a wide labor instability. Finally, it has been determined a significant relationship of organizational climate on the performance of the employees of the district municipality of morales, because by maintaining regular climate, the performance of employees would behave similarly, this due to political, benefits, job security, among others affect the actual performance of the employees of the district municipality of morales.